Interdisciplinary and transdisciplinary research and practice: Balancing expectations of the 'old' academy with the future model of universities as 'problem solvers'. (14th July 2019) - Fam, Dena; Clarke, Elizabeth; Freeth, Rebecca; Derwort, Pim; Klaniecki, Kathleen; Kater‐Wettstädt, Lydia; Juarez‐Bourke, Sadhbh; Hilser, Stefan; Peukert, Daniela; Meyer, Esther; Horcea‐Milcu, Andra‐Ioana
Abstract: Academics are increasingly required to balance the expectations of the 'old' academy with a future model of universities as interdisciplinary and transdisciplinary 'problem solvers'. This paper highlights changing expectations of academics in producing alternative research outcomes in collaborative, practice‐based research. Through a series of workshops with 20 researchers, preferred research outcomes and tensions in achieving these outcomes were identified. The tensions identified are presented as three dichotomies comprising the tension between: (a) 'I versus We' ‐ individual versus team expectations & outcomes. (b) Disciplinary outcomes versus inter‐/transdisciplinary outcomes. (c) Learning versus research objectives for the students and academics involved. These tensions reflect the authors' experiences of working in three international sustainability projects, drawing on lessons learned from these projects, with recommendations for universities seeking to implement interdisciplinary and transdisciplinary doctoral and postdoctoral programmes. Recommendations include the need for formal and informal leadership models, strong communication skills, empathy and willingness to learn from each other. A need for more systemic changes within university administration to better reward and value the breadth and depth of collaborative work, while facilitating open learning cultures and practice‐oriented learning opportunities and curricula across faculties was also identified. Zusammenfassung: Akademiker werden zunehmend aufgefordert, die Erwartungen der 'alten' Akademie mit einem Zukunftsmodell der Universitäten als inter‐ und transdisziplinäre 'Problemlöser' in Einklang zu bringen. Diese Arbeit beleuchtet die sich ändernden Erwartungen von Wissenschaftlern, alternative Forschungsergebnisse in einer kollaborativen, praxisorientierten Forschung zu erzielen, die disziplinübergreifend ist. In einer Reihe von Workshops mit 20 Forschern wurden bevorzugte Forschungsergebnisse sowie Spannungen bei der Erzielung von Ergebnissen in interdisziplinären und transdisziplinären Projekten ermittelt. Die von den Teilnehmern identifizierten Spannungen wurden als drei Dichotomien dargestellt, einschließlich der Spannung zwischen: 1. 'Ich gegen Wir' ‐ Individuelle gegen Team‐Erwartungen und –Ergebnisse. 2. Disziplinarergebnisse versus inter‐/transdisziplinäre Ergebnisse. 3. Lernen versus Forschungsziele für die beteiligten Studierenden und Wissenschaftler. Im Vordergrund dieser Spannungen als Dichotomien stellen wir die Erfahrungen der Autoren vor, die in drei internationalen interdisziplinären und transdisziplinären Projekten im Bereich Nachhaltigkeit gearbeitet haben. Aus diesen Projekten ziehen wir Erkenntnisse mit Empfehlungen für Hochschulen, die inter‐ und transdisziplinäre Doktoranden‐ und Postdoktorandenprogramme durchführen möchten. Zu diesen Empfehlungen gehören die Notwendigkeit sowohl formeller als auch informeller Führungsmodelle, ausgeprägte Kommunikationsfähigkeiten, Einfühlungsvermögen und die Bereitschaft, voneinander zu lernen. Darüber hinaus heben wir die Notwendigkeit hervor, Zeit und Ressourcen zu investieren, um eine gemeinsame Terminologie für Problemstellungen und kollaborative Praktiken zu entwickeln. Dies kommt zu der Notwendigkeit für mehr systematische Änderungen innerhalb der Universitätsverwaltung hinzu, um die Breite und Tiefe der Zusammenarbeit besser zu honorieren und zu würdigen und gleichzeitig offene Lernkulturen sowie praxisorientierte Lernmöglichkeiten und Lehrpläne fakultätsübergreifend zu fördern und den Forschungszeithorizont für inter‐ und transdisziplinäre Forschung zu erweitern.